Study of temporal variability (2004-2023) in cassava production (Manihot esculenta Crantz) in the Queimadas municipality, Paraíba - Sousa, Welinagila Grangeiro de; Maddalena, Anddreza; Lima, Santana Lívia de; Lima, Ricardo da Cunha Correia; Alves, Lionézia Freire; Araujo Neto, Antenor Pereira de; Barbosa , Maykon Douglas Gomes; Isidro, Renato; Abreu, Khyson Gomes; Gouveia, Tulio Cavalcanti de Matos; Pontes, Germana Pessoa de; Albuquerque Jr., Aldo Muniz de; et al. (Brazilian Journal of Production Engineering, 2026)
Cassava is a crop of socioeconomic and environmental importance in Brazil, especially in the Northeast region. Its roots are rich in starch, used in human and animal nutrition, and as a raw material in industry. Factors such as the use of low-yield genetic materials, inadequate soil management practices, and the occurrence of pests and diseases compromise the crop. Therefore, the objective of this study was to analyze the production performance of cassava in Queimadas, Paraíba, from 2004 to 2023. The aim was to identify factors that influenced the evolution of local production, to determine which aspects determined the variations in cassava production, and how this can guide strategies and public policies for the sustainable strengthening of the crop. The analysis of the temporal variability of production showed that there was no significant progress, indicating the need for attention to the factors that influence the crop's productivity and profitability, reinforcing the urgent need to adopt new management techniques. Investments in producer training, genetic improvement, appropriate soil management, and rational use of irrigation are alternatives. Furthermore, encouraging agro-industrialization and the use of by-products is also promising for adding value and strengthening the local economy, making the activity more sustainable and competitive.
Keywords: Roots; Factors; Enhance